2015
DOI: 10.1159/000373983
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Bacteria Affect Danio rerio Development by the Modulation of Maternal Factors Involved in Autophagic, Apoptotic and Dorsalizing Processes

Abstract: Background/Aims: Probiotic strains have been recognized to exert important roles in many biological systems, including immune response, growth, development and reproduction. However, to date, no studies have focused either on the relation among probiotics and maternal factors or on probiotics' ability to qualitatively and/or quantitatively modulate maternal transcripts. Methods: In this study, the effects of Lactobacillusrhamnosus administered to parental fish on the control of maternal factors involved in aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 67 publications
1
17
1
Order By: Relevance
“… 47 in the present study, the lower TAG content found in zebrafish fed a HFD-P and MFD-P suggests the probiotic’s capability to modulate transcriptional process involved in the regulation of TAG metabolism. Contrary to what previously found in zebrafish larvae 10 , 48 , the findings we obtained with adult zebrafish are supported by the loss of weight observed in the adult fish fed a HDF-P and MFD-P compared to the control ones and suggest the capability of the probiotic to successfully prevent weight gain, thus reducing the high-fat-diet induced obesity.…”
Section: Discussioncontrasting
confidence: 94%
“… 47 in the present study, the lower TAG content found in zebrafish fed a HFD-P and MFD-P suggests the probiotic’s capability to modulate transcriptional process involved in the regulation of TAG metabolism. Contrary to what previously found in zebrafish larvae 10 , 48 , the findings we obtained with adult zebrafish are supported by the loss of weight observed in the adult fish fed a HDF-P and MFD-P compared to the control ones and suggest the capability of the probiotic to successfully prevent weight gain, thus reducing the high-fat-diet induced obesity.…”
Section: Discussioncontrasting
confidence: 94%
“…Autophagy is the primary intracellular catabolic process wherein malfunctioning cytoplasmic proteins or disabled organelles are delivered to the lysosomes for degradation and recycling [1,2]. Basal levels of autophagy have been demonstrated to be involved in certain types of physiologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is associated with mitophagy 30,31 . Knockdown of Drfundc1 decreased expression of the apoptosis-related genes baxb , bcl2a , bcl2b , and caspase3a 32,33,45,47,48 , contrasting to results of 293 T cells due to ectopic expression of Drfundc1 . This means that Drfundc1 knockdown interferes with apoptosis in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 74%
“…Authors of several studies have claimed that autophagy tends to be accompanied by a certain degree of apoptosis 30,31 . We therefore measured expressions of the following autophagy- and apoptosis-related genes: atg5 , atg7 , atg12 , autophagy and beclin 1 regulator 1a ( ambra1a ), ambra1b , nucleoporin 62 ( p62 ), beclin1 , bcl2a , bcl2b , baxa , baxb , caspase3a , caspase9, p53 , and forkhead transcription factor 3a ( fox3a ) 32,33 .…”
Section: Resultsmentioning
confidence: 99%